(3GdLhgQ GdeUhf hGdSQ GdeQbhe ajeG JfJLg GdNdhI ef GdCSQGQ hGdYdhes - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s ((3jhSa Hf SQGL GdOjf Hf HOQ GdOjf GdTQfHdGdi GdMfai s)
(3ChdgG (B:s
(3hHYO agPG cJGH fajS djS ai PNGFQ Sdhc GdOfjG eKdg hSejJg HGdLhgQ GdeUhf hGdSQ GdeQbhe ajeG JfJLg GdNdhI ef GdGSQGQ hGdYdhe s
(3BNQgG (B:s
(3jfJgi HMOjKg Ydi (B( (3eG JfJLg GdNdhI ef Ydhe ShQI GdfGS (B) s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HBNQg ELGRGJ GdcKjQ ef GdTjhNs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs